A Comprehensive Review of the Effects of Hyoscine Butylbromide in Childhood - Vázquez Frias, Rodrigo; Hörning, André; Boggio Marzet, Christian; Michel, Martin C. (Journal of Clinical Medicine, 2025)
Background/Objectives: Hyoscine butylbromide (HBB) is a spasmolytic drug classified as indispensable by the World Health Organization. While mostly used in adults, it is also approved for use in adolescents and children aged 6 years and older. We have comprehensively reviewed the efficacy and safety of HBB in approved and off-label childhood indications. Results: Childhood studies covered an age range starting as early as 2 days. A randomized controlled trial (RCT) found a similar efficacy compared to paracetamol in the approved indication of abdominal cramps and pain. Among off-label uses, several studies demonstrate efficacy in general anesthesia and various diagnostic procedures, but the largest body of evidence relates to use in childbirth/labor, including 17 RCTs. While these largely focused on efficacy outcomes on the mother, fetal safety outcomes were reported in 12 of these studies, mostly as effects on the APGAR score and/or heart rate. The overall evidence supports safety in infants and children including those younger than the approved use age of 6 years and older. Conclusions: While only limited pediatric efficacy data from RCTs are available in the approved indications, data from thousands of patients in RCTs, case series, and non-randomized trials do not raise concerns on the safety and tolerability of HBB in childhood. Additional dedicated childhood studies, particularly RCTs, on efficacy are recommended.
CRIS-Team Scopus Importer:2025-05-23
Keywords: abdominal cramps; abdominal pain; childbirth; children; hyoscine butylbromide; infants; vomiting